Legal Disputes in Infrastructure Projects Involving Foreign Companies - M. Oktariansyah; Sami’an Sami’an; Sarwono Hadjomuldjadi; Ganis Vitayanty Noor (Interdisciplinary Social Studies, 2025)
The involvement of foreign companies in infrastructure development in Indonesia has increased rapidly over the last two decades, driven by growing needs for capital, technology, and advanced project management standards. However, the complexity of cross-jurisdictional issues and divergent interests among states, state-owned enterprises, investors, and contractors heightens the potential for intense legal disputes. This research examines the characteristics of disputes, their root causes, national and international regulatory frameworks, dispute resolution mechanisms, case patterns, and recommendations for strengthening project governance. Studies show that dispute roots extend beyond technical-contractual matters to include political factors, regulatory disharmony, information asymmetries, and weak contract administration. The research concludes that preventing disputes through appropriate risk allocation, regulatory transparency, and enhanced government capacity represents fundamental steps to mitigate the economic and political costs of high-value infrastructure disputes. The findings imply that, to enhance Indonesia’s attractiveness to foreign investors, policymakers should prioritize regulatory harmonization, institutionalize early dispute prevention mechanisms such as the Dispute Avoidance/Adjudication Board (DAAB), and streamline enforcement of international arbitration awards.